Immunosupressant Effect of the Extract of Tridax procumbens on Lymphocyte Cells Line from Patients with Systemic Lupus Erythematous: Immunoglobulin Gbiomarker - Abdul Khairul Rizki Purba; Endang Mahati; Yolanda Dyah Kartika; Indwiani Astuti; Nyoman Kertia (Journal of Tropical Pharmacy and Chemistry, 2013)
Systemic Lupus Erythematous (SLE) is one of the major autoimmune diseases that can cause severe damage to the tissues and organs in the body and lead to high mortality rates. The clinical manifestations are characterized by the production of autoantibody immunoglobulin G (Ig G) that fights component of the nucleus. The present scientific information issues about peculiar property of Tridax procumbens as immunosuppressant by inhibiting enzyme of cyclooxygenase-2 (COX-2) on surface of B cells. This study approved effect of the extract of Tridax procumbens on human lymphocytes cells line with SLE disease. The aim of this study was to approve effect of extract of Tridax procumbens in suppressing Ig G concentration from patient with stable SLE and patient with active SLE in vitro. This study was an in vitro experimental design on lymphocytes cell line that was isolated from whole blood patient with stable SLE and active SLE. Lymphocyte cells from healthy volunteer were also collected as control. American Rheumatism Association Diagnostic was used for inclusion criteria.Tridax procumbens was extracted with maceration method in solution of ethyl acetate. The extract was divided in several doses as immunosuppressant i.e.1000; 250; 62.5; 31.25; 15.13; and 3.91 µg/mL. Supernatant of the cultured cells was collected and examined for measuring Ig G concentration as secretion from activated B cells by ELISA. Ethical clearance had been completed before this study started. The extract of Tridax procumbens significantly suppressed Ig G secretion in patient with stable SLE at dose over 62.5 µg/mL, but Ig G concentration in patient with active SLE was significantly increased when compared with control. Furthermore from the analysis, effect of the Tridax procumbens extract on Ig G concentration followed dose dependent response. In in-vitro study, the extract of Tridax procumbens could significantly suppress Ig G secretion in healthy volunteer and patient with stable SLE. Otherwise, the extract does not suggest for patient with active SLE and it needs caution in use and investigation in-depth. Keywords: SLE, Tridax procumbens, immunoglobulin G ABSTRAK Penyakit Systemic Lupus Erythematous (SLE) merupakan salah satu penyakit autoimun yang sering menyebabkan kerusakan jaringan dan organ sehingga angka kematiannya tinggi. Karakteristik patognomonik penyakit SLE ditandai ada produksi auto antibody immunoglobulin G (Ig G) yang melawan komponen nukleosom tubuh sendiri. Penelitian ilmiah terbaru menunjukkan bahwa ekstrak Tridax procumbens memiliki efek imunosupresan melalui hambatan enzim cyclooxygenase-2 (COX-2) pada permukaan sel B. Pada studi ini menguji efek ekstrak Tridax procumbens pada cells line limfosit dari pasien SLE. Tujuan penelitian ini adalah mengetahui efek ekstrak Tridax procumbens dalam menekan konsentrasi Ig G pasien dengan SLE stabil dan pasien dengan SLE aktif secara in vitro. Penelitian ini merupakan penelitian eksperimen pada cell line limfosit yang diisolasi dari whole blood pasien dengan SLE stabil dan SLE aktif. Kelompok kontrol limfosit diambil dari sukarelawan sehat. Kriteria inklusi pasien yang mengikuti penelitian ini berdasarkan kriteria diagnostik American Rheumatism Association. Tridax procumbens diekstraksi dengan metode maserasi larutan etil asetat. Ekstrak dibagi menjadi beberapa dosis sebagai imunosupresan yaitu 1000; 250; 62,5; 31,25; 15,13; dan 3,91 µg/mL. Supernatan dari sel kultur dikoleksi dan diukur konsentrasi Ig G yang merupakan sekresi sel B dengan menggunakan metode ELISA. Persetujuan etik dilakukan sebelum penelitian dilakukan. Ekstrak Tridax procumbens menekan sekresi Ig G pasien dengan SLE stabil pada dosis diatas 62,5 µg/mL, namun konsentrasi Ig G dari pasien dengan SLE aktif meningkat secara signifikan dibandingkan dengan kontrol. Efek ekstrak Tridax procumbens pada konsentrasi Ig G mengikuti dose dependent response. Pada penelitian ini, ekstrak Tridax procumbens dapat menekan sekresi Ig G dari pasien dengan SLE stabil dan sukarelawan sehat. Pemberian ekstrak Tridax procumbens tidak dianjurkan pada pasien dengan SLE aktif, namun hal ini masih membutuhkan penelitian lebih mendalam. Keywords: SLE, Tridax procumbens, imunoglobulin G